APLIKASI TEKNOLOGI FERMENTASI KULIT BUAH COKLAT UNTUK MENINGKATKAN KUALITAS PAKAN TERNAK DI NAGARI LURAH AMPALU KECAMATAN VII KOTO PADANG PARIAMAN - Fridarti Fridarti; Sri Mulyani (Jurnal Hilirisasi IPTEKS, 2020)
Nagari Lurah Ampalu is one of the largest cocoa production centers (cacao) in West Sumatra, thus the waste of cocoa pods is quite widely available but has not been optimally utilized. To provide information about simple technology that can be used in processing this waste. One of the technologies is fermentation in this community service using extension methods (interactive dialogue) between the community and the team on: fermentation technology, utilization of cocoa waste, good livestock maintenance and problems faced by the community. The results activity is high community enthusiasm, low education, with long enough experience. The fermentation results are quite good (smell good, the color does not change from the origin, and there is no fungus) and the results of the observations when given to livestock are good enough where the livestock are very fond of it thus the consumption rate increases and weight gain increases with the provision of 25% of forage.